Influenza vaccine uptake, COVID-19 vaccination intention and vaccine hesitancy among nurses: A survey. (February 2021) - Kwok, Kin On; Li, Kin-Kit; WEI, Wan In; Tang, Arthur; Wong, Samuel Yeung Shan; Lee, Shui Shan
Abstract: Background: A healthy healthcare system requires healthy healthcare workers. Protecting healthcare workers including nurses against COVID-19 is crucial, and vaccination could be a viable future option. However, vaccine hesitancy remains a global challenge. Nurses, as a trustworthy and creditable source of vaccine-related information, may build public confidence in vaccination. Hence, research on vaccine hesitancy among nurses is warranted. Objectives: This study estimated nurses' influenza vaccination behaviors and intention to receive COVID-19 vaccine when available, and examined their corresponding 5C psychological antecedents (confidence, complacency, constraints, calculation, and collective responsibility). To investigate the impact of COVID-19-related work demands, the mediation effects of work stress on the association between work demands and COVID-19 vaccination intention were also examined. Design: Cross-sectional online survey Settings: Nurses were invited to participate via the promotion of a professional nursing organization and by personal referrals during the COVID-19 outbreak in Hong Kong between mid-March and late April 2020. Participants: 1, 205 eligible nurses (mean age = 40.79, SD  = 10.47; 90% being female) were included in the analyses. Methods: Demographics, influenza vaccination, intention to have COVID-19 vaccine, the 5C vaccine hesitancy components, work stress and COVID-19-related work demands (insufficient supply of personal protective equipment, involvement in isolation rooms, and unfavorable attitudes towards workplace infection control policies) were reported in the survey. Results: The influenza vaccine uptake rate and the proportion intending to take COVID-19 vaccine were 49% and 63%, respectively. Influenza vaccination was associated with working in public hospitals and all 5C constructs (more confidence, more collective responsibility and less complacency, constraints, and calculation), whereas stronger COVID-19 vaccination intention was associated with younger age, more confidence, less complacency and more collective responsibility. COVID-19-related demands were associated with greater work stress, and hence stronger COVID-19 vaccination intention. Conclusion: The potential uptake rate of COVID-19 vaccine among nurses was suboptimal to achieve herd immunity. The 5C constructs were useful in predicting influenza vaccination and, to a lesser extent, the intention to take COVID-19 vaccine. The uncertain attributes such as effectiveness, side effects, and effective duration of the COVID-19 vaccine may contribute to this discrepancy. With less work stress among nurses in the post-pandemic period, the intention to take COVID-19 vaccine will likely drop. The 5C constructs should be infused in vaccination campaigns. While a COVID-19 vaccine could be ready soon, the nursing profession may not be ready to accept it. More research work is needed to boost the uptake rate. Tweetable abstract: Less than two-third of nurses intended to take COVID-19 vaccine when available. While a COVID-19 vaccine could be ready soon, nursing profession is not ready to accept it.